2018
DOI: 10.12973/iji.2018.1115a
|View full text |Cite
|
Sign up to set email alerts
|

The Courseware of Discontinuous Nature of Matter in Teaching the States of Matter and Their Changes

Abstract: Among three levels of chemical representation, the sub-microscopic level is the most difficult to learn by students. To solve the problem, it is assumed that the concept of the discontinuous nature of matter or particle concept should be mastered initially by students before they learn sub-microscopic representations of further chemical phenomena. 131 junior high school students from two schools participated in this study. The study was carried out by implementing structureoriented chemistry teaching on the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
3
8
0
Order By: Relevance
“…The prerequisite concepts for states of matter and their changes on discontinuity of matter and dynamic property of particles will help the prospective teachers to comprehend the topic. This is in line with previous research (Sopandi et al, 2018) indicating that students' good comprehension of discontinuity of matter can help them to understand the states of matter and their changes at the submicroscopic level. It is expected that by understanding the discontinuity of matter and the dynamic properties of particles, prospective teachers can apply that understanding to various concepts and other related representations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The prerequisite concepts for states of matter and their changes on discontinuity of matter and dynamic property of particles will help the prospective teachers to comprehend the topic. This is in line with previous research (Sopandi et al, 2018) indicating that students' good comprehension of discontinuity of matter can help them to understand the states of matter and their changes at the submicroscopic level. It is expected that by understanding the discontinuity of matter and the dynamic properties of particles, prospective teachers can apply that understanding to various concepts and other related representations.…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study showed that there were still misconceptions about states of matter and their changes. This finding is in line with previous findings that showed' Nature of Particle Substance' is one of the concepts in which learners have the most alternative concepts (Bilgin et al, 2017;Sopandi, 2017b;Sopandi et al, 2018). Correspondingly, conception change is not an easy task and misconceptions are difficult to correct (Barke et al, 2009;Suparno, 2013: 7;Setyaningrum, 2016).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although the microscopic level or particle nature of matter is a heart to learn science concepts to the next level of understanding science [22]. Besides the heart of science, microscopic level also helps students to give a comprehensive understanding of the scientific phenomena [20,23,24]. This problem is not only happening in students at the pre-service teacher but also the teachers [25].…”
Section: B Discussionmentioning
confidence: 99%
“…Whereas, drawing is a useful approach to probe understanding in students learning and enables the researcher to reveal the student's and teacher's qualities of understanding that can be hidden through other research procedures [19]. Teaching science should give change for students to represent their understanding not only verbally but also visually [20]. The drawing also involves conceptual knowledge that serves as a way of capturing students' thinking, understanding, and shift [21].…”
Section: Related Work/literature Reviewmentioning
confidence: 99%